Transient Response and Firing Behaviors of Memristive Neuron Circuit - Fang, Xiaoyan; Tan, Yao; Zhang, Fengqing; Duan, Shukai; Wang, Lidan (Frontiers in Neuroscience, 2022)
The signal transmission mechanism of the Resistor-Capacitor (RC) circuit is similar to the intracellular and extracellular signal propagating mechanism of the neuron. Thus, the RC circuit can be utilized as the circuit model of the neuron cell membrane. However, resistors are electronic components with the fixed-resistance and have no memory properties. A memristor is a promising neuro-morphological electronic device with nonvolatile, switching, and nonlinear characteristics. First of all, we consider replacing the resistor in the RC neuron circuit with a memristor, which is named the Memristor-Capacitor (MC), then the MC neuron model is constructed. We compare the charging and discharging processes between the RC and MC neuron circuits. Secondly, the synchronous and asynchronous activities of the RC and MC neuron circuits are performed. Finally, two models are compared under the different external stimuli. Extensive experimental results suggest that the charging and discharging speed of the MC neuron circuit is faster than that of the RC neuron circuit. The synchronous and asynchronous phenomena in the two neuron circuits reproduce nonlinear dynamic behaviors of the biological neurons. Given sufficient time and proper external stimuli, the RC and MC neuron circuits can produce the action potentials.